ЗНАЧЕННЯ САМОАКТУАЛІЗАЦІЇ МАЙБУТНЬОГО ВЧИТЕЛЯ .МУЗИКИ У ПРОЦЕСІ ПРОФЕСІЙНОЇ ПІДГОТОВКИ (Педагогіка вищої та середньої школи, 2010)
The article «The mining of self-actualization future teacher of music is in a process of the professional training» has education, which must be trended to the profession-personal self-actualization or to the realization and the development of creative potential of every student, to promote his personal professional advance and it's an important stage for the way of the student's personal development and the decision ofprofessional prospects, ft is studied the motivation of the aspiration future teacher of music to self-actualization. It is discovered the meaning of selfactualization and the demands to it.